The Effect of Combining 2D and 3D Moving Particles on Hybrid Motion Graphics - Alamarat, Yazan Ibrahim; Al-Omari, Hussein Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to evaluate the level of complexity involved in integrating 2D and 3D techniques and evaluating the utility of this approach for designers in generating innovative motion designs,. It also aims to examine the design methodology employed in the creation of 2D and 3D motion graphics. Methods: The study used the descriptive- analytical approach. It also used the quantitative approach based on understanding the effect of combining 2D and 3D moving particles in designing new and innovative designs and determining the relevant terminology and concepts to create 2D and 3D moving graphics. A questionnaire was also distributed to 200 professional and specialized motion graphic designers to test the possibility of combining contemporary designs together. Results: The study’s quantitative results showed a positive and significant reality for employing the combination of the 2D and 3D elements in motion graphics with a high likelihood of implementation by the designer. The study results also showed a high average in producing cutting-edge styles via combining 2D and 3D elements in motion graphics. Conclusion: The study highlights the importance of conducting an accurate evaluation of the various variables to achieve the best results during the process of designing hybrid motion graphics which combine 2D and 3D particles. The study also states that the success of the combination process depends on the effectiveness of the visual style of the hybrid graphic designs and the effects, structure and motion in creating integrated images that effectively transmit the emotional story behind those designs.